Plastic design and second-order analysis of steel frames (with 312 illustrations, includes two diskettes - W F Chen (Springer-Verlag, 1995)
The book presents the plastic methods in as simple a manner as possible. It aims squarely for students of tructural engineering who are familliar with the processes of elastic analysis and design of building frames. The book includes two computer programson two diskettes: one for the first-order analyses and the other for the second-order plastic hinge analysis of planar frame design. The diskettes also contain the complete FORTRAN source-code listing for the second-order plastic-hinge analysis, enabling the user to customize the program